Virtual Deficits and the Patinkin Effect - Cardoso, Eliane (Washington, D.C. : International Monetary Fund, 1998)
The paper develops a model of inflationary finance that defines the fiscal deficit as a function of the virtual deficit-a deficit that would be observed if inflation were zero. It studies the negative relationship between the inflation rate and real government expenditures-the Patinkin effect. The model outperforms others in explaining four-digit inflation rates that never explode into hyperinflation. It also explains how apparently expansionist fiscal policies end in real deficits that are small and compatible with the small amount of seigniorage that can be collected at high inflation rates. Finally, it applies the model to the case of Brazil.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet